The aliens in the economy and society of London in the 14th century: Interaction and conflicts - Leshtaev, Dmitry Valerievich (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
The article examines the place of aliens in the economy and society of 14th-century London. Based on a wide range of sources and research literature, the author identifies the main groups of foreign trading partners of the English capital and the attitude of municipal society towards them, traces the history of the City’s struggle to maintain its privileges in relations with aliens in the 14th century, and characterizes the changes in the economic situation against the backdrop of the developing confrontation. Examples of the integration of aliens into 14th-century London society are given, highlighting a number of niches they were mastering, including the area of illegal activities. A conclusion is made about the importance ofthemerchant strangers’ presence in Londonforthe development of England’sforeign economic relations andthe accompanying change in society’s attitude towards foreignmerchants, which becamemore negative, with calls for stimulating the development of national trade.